2013
DOI: 10.1186/1750-1172-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dysferlinopathy with deflazacort: a double-blind, placebo-controlled clinical trial

Abstract: BackgroundDysferlinopathies are autosomal recessive disorders caused by mutations in the dysferlin (DYSF) gene encoding the dysferlin protein. DYSF mutations lead to a wide range of muscular phenotypes, with the most prominent being Miyoshi myopathy (MM) and limb girdle muscular dystrophy type 2B (LGMD2B).MethodsWe assessed the one-year-natural course of dysferlinopathy, and the safety and efficacy of deflazacort treatment in a double-blind, placebo-controlled cross-over trial. After one year of natural course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 28 publications
1
72
0
2
Order By: Relevance
“…Treatment response to steroid in 6 unrelated patients with sarcoglycanopathy. did not improve muscle strength 23 . Furthermore, there was a trend of worsening muscle strength in the group under deflazacort treatment, which recovered after discontinuation of the study drug.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Treatment response to steroid in 6 unrelated patients with sarcoglycanopathy. did not improve muscle strength 23 . Furthermore, there was a trend of worsening muscle strength in the group under deflazacort treatment, which recovered after discontinuation of the study drug.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, there was a trend of worsening muscle strength in the group under deflazacort treatment, which recovered after discontinuation of the study drug. In addition, patients showed a broad spectrum of steroid side effects 23 . Regarding the response to corticosteroids of the cardiac function, our study showed a mild improvement of the ventricular ejection fraction in two patients and in three patients the cardiac function remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…After a 2% reduction was detected in muscle strength on the Clinical Investigation of Duchenne Dystrophy scale 1 year later, the patients were divided into steroid (deflazacort at 1 mg/kg/day for 1 month, then 2 mg/kg every other day for 6 months) and placebo groups in a doubleblinded method. It was reported at the end of the study that the steroid did not display the benefit that it provided in Duchenne muscular dystrophy and, on the contrary, adverse effects were observed in the steroid group on the severity of disease, loss in muscle strength, and quality of life scales (1). Thus, the importance of differentiation from polymyositis was emphasized once again and it was reported that the initiation of unnecessary steroid treatment adversely affected the disease.…”
Section: Discussionmentioning
confidence: 98%
“…The serum creatine kinase (CK) level is quite high, even in the preclinical period. Typically, a dystrophic pattern is observed on muscle biopsy and is often accompanied by inflammatory changes (1). Here we report a case of dysferlinopathy in a patient who had been followed up owing to an increased CK level since she was 1 year old and who had received steroid and azathioprine treatment for 3 years with a diagnosis of polymyositis, which was made as a result of a muscle biopsy performed 7 years ago in Syria.…”
mentioning
confidence: 94%
“…Попытки лечения прогрессирующих наследствен-ных КПМД стероидными препаратами не принесли успеха [60]. Тем не менее в настоящий момент на жи-вотных моделях проводятся исследования новых видов терапии мышечных дистрофий, в том числе и кальпа- …”
Section: контрак-туры/ сколиозunclassified